2013
DOI: 10.1186/1475-2875-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin resistance in rodent malaria - mutation in the AP2 adaptor μ-chain suggests involvement of endocytosis and membrane protein trafficking

Abstract: BackgroundThe control of malaria, caused by Plasmodium falciparum, is hampered by the relentless evolution of drug resistance. Because artemisinin derivatives are now used in the most effective anti-malarial therapy, resistance to artemisinin would be catastrophic. Indeed, studies suggest that artemisinin resistance has already appeared in natural infections. Understanding the mechanisms of resistance would help to prolong the effective lifetime of these drugs. Genetic markers of resistance are therefore requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 69 publications
0
79
0
Order By: Relevance
“…A recent review provides a more detailed discussion of possible roles for PI3P/PI3K in ART resistance [60]. Interestingly, a recent study with ART-pressured, resistant rodent parasites also implicates an important role for altered hemoglobin endocytosis in ART resistance [61]. …”
Section: What Are the Targets Of Activated Arts?mentioning
confidence: 99%
“…A recent review provides a more detailed discussion of possible roles for PI3P/PI3K in ART resistance [60]. Interestingly, a recent study with ART-pressured, resistant rodent parasites also implicates an important role for altered hemoglobin endocytosis in ART resistance [61]. …”
Section: What Are the Targets Of Activated Arts?mentioning
confidence: 99%
“…Whole-genome sequencing of ART-pressured P. chaubaudi parasites referred to above [74] identified a single mutation: I568T in the mu chain of the AP2 adaptor complex (PCHAS_143590) [79]. In humans the AP2 complex is involved in clathrin-mediated endocytosis [80].…”
Section: The Roles Of Ubiquitin Ligases and Deubiquitinating Enzymes mentioning
confidence: 99%
“…In humans the AP2 complex is involved in clathrin-mediated endocytosis [80]. Homology modeling studies predict that the I568T mutation alters binding affinity of the PcAP2 μchain to cargo protein undergoing endocytosis [79]. Analysis of parasite isolates from ACT-treated Kenyan children suggested an increased prevalence of S160N/T mutations in PfAP2-μ (PF3D7_1218300) or a E1528D mutation in PfUBP1 in parasites surviving ACT treatment [81].…”
Section: The Roles Of Ubiquitin Ligases and Deubiquitinating Enzymes mentioning
confidence: 99%
“…Recent published data from studies of artemisinin resistance in the rodent parasite Plasmodium chabaudi has identified a new candidate locus , pcap2mu , encoding the clathrin-associated μ adaptor protein 2 [36]. These authors described potentially important sequence diversity in the P. falciparum homologue, pfap2mu (PF3D7_1218300), between codons 146 and 437, in a series of clinical isolates.…”
Section: Introductionmentioning
confidence: 99%